2013
DOI: 10.1155/2013/293809
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Bearing Capacity of Shallow Foundation on Geogrid Reinforced Silty Clay and Sand

Abstract: The present study investigates the improvement in the bearing capacity of silty clay soil with thin sand layer on top and placing geogrids at different depths. Model tests were performed for a rectangular footing resting on top of the soil to establish the load versus settlement curves of unreinforced and reinforced soil system. The test results focus on the improvement in bearing capacity of silty clay and sand on unreinforced and reinforced soil system in non-dimensional form, that is, BCR. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 28 publications
2
20
0
2
Order By: Relevance
“…The Open Access Journal of Science and Technology Figure 4: Soil classification scale based on particle size of local earth materials [11].…”
Section: Results Of Soil Classification Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The Open Access Journal of Science and Technology Figure 4: Soil classification scale based on particle size of local earth materials [11].…”
Section: Results Of Soil Classification Testmentioning
confidence: 99%
“…When supporting lightly loaded structures, the effect of significant changes in shrinkage of soils with high shrinkswell potential can be severe [20]. Hence, it is important to provide analysis to reliably estimate the volume change behaviour of soils with different cement content in field [11].…”
Section: Introductionmentioning
confidence: 99%
“…where 15 is the settlement of the unreinforced footing and is the settlement of the reinforced footing at the footing pressure of unreinforced one having a settlement value of 15 . Figures 14 and 15 show the comparison of PCS factors with respect to the footing with granular fill (0.50-(0.75 ) and 0.75-(0.75 )).…”
Section: Series IIImentioning
confidence: 99%
“…The test results had shown that use of granular fill and geogrid for reinforced soil footings (RSF) has considerable effects on the subgrade modulus and bearing capacity. Very recently Kolay et al [15] investigated the improvement in the bearing capacity of silty clay soil with thin sand layer on top and placing geogrids at different depths. The test results revealed that the bearing capacity for the soil increases with the increase in number of geogrid layers.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of products (geogrid, geotextile, geocell, geomebrane, etc.) are available in engineering process .Each product is designed to solve a particular range of civil engineering problems [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%